The Plurimodal Approach in Music Therapy - Schapira, Diego; Hugo, Mayra (Voices: A World Forum for Music Therapy, 2005)
We will discuss the Plurimodal Approach in Music Therapy, which we have been developing and using for several years. This approach is currently taught as a graduate course at the University of Buenos Aires (Argentina) and it has been utilized in other Latin American countries such as Uruguay, Chile, Peru, Colombia, México, and Brazil. We have studied different music therapy theories and we realize there are important connections between them. We try to build bridges between different theoretical lines that allow us to work better with a larger theoretical basis to support our actions with our clients.